SWOT Analysis of the Impact of Education Financing on the Quality of Education at State Primary School 001 Gunung Tabur - Risna Herjayanti; Eli Sutrinaniati; Junainah; Mulyati (PT ARRUS Intelektual Indonesia, 2024)
Educational financing is a crucial aspect of education, especially regarding educational quality. This study aims to analyze the SWOT (Strengths, Weaknesses, Opportunities, Threats) of educational financing at SD Negeri 001 Gunung Tabur and its impact on educational quality. The research method used is descriptive qualitative with SWOT analysis techniques. Data collection techniques were conducted by distributing questionnaires to educators and parents. The analysis results show that adequate financing has provided strength in the provision of good educational facilities. However, weaknesses are seen in government policies that have not covered all the school's needs. Opportunities for improving educational quality can be optimized through increased allocation of funds from the government and cooperation with the private sector. On the other hand, threats from government policy uncertainty can hinder the achievement of the desired educational quality. In conclusion, educational financing has a significant impact on educational quality at SD Negeri 001 Gunung Tabur, and better management and utilization of existing opportunities are needed to optimize this positive impact.